Pedal-driven [videorecording (DVD)] - Howell, Jamie; Howell, Jamie (Docurama Films : distributed by New Video, 2013)
Delves into the escalating conflict between mountain bikers hungry to ride and the federal land managers charged with protecting the public lands. It will take you behind both sides of this confrontation, riding with the freeriders and chasing them down with the rangers, in an exploration of issues increasingly important to all Americans.